CAPABILITY OF SOIL PHOSPHATE-SOLUBILIZING BACTERIAL STRAINS TO COLONIZE WHEAT ROOTS - К. В. Лаврентьєва; Н. В. Черевач; А. I. Вінніков (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2010)
During microvegetative investigation at wheat plants it was shown that Enterobacter dissolvens and Pseudomonas putida strains survive better in the media with insoluble tricalciumphosphate in contrast to medium with phosphate ion content. The strains of soil bacteria have high adhesive features to the plant roots as 1g of wheat root contains more than 5.7 lg of colony forming units. It was shown that the strains of P. putida colonize wheat roots more actively than E. dissolvens strains, that is characteristically for this genus of bacteria.